GEORGIA: POLITICAL PARTIES BEFORE AND AFTER THE ROSE REVOLUTION - GAKHOKIDZE, Ekaterine (CENTRAL ASIA AND THE CAUCASUS, 2005)
The country is heading toward democracy and busy consolidating its institutions, so it is paying particular attention to fair and legitimate elections and encouraging the appearance of strong political parties as one of the guarantors of democracy and stability. Indeed, an election is a political procedure which allows a nation to ensure a peaceful transition of power and mobilize its citizens. It allows the voters and political forces to use their constitutional right to take part in the country’s political life. At times, these forces fail to recognize their responsibility to the voters. As a result, an increasingly larger share of the country’s population is becoming disillusioned by representative democracy and elections as its political institution. It often happens that far from creating public harmony, elections generate even wider political gaps or even sharper social conflicts. This was vividly demonstrated by the Rose Revolution, a direct response to the massive falsifications of the parliamentary elections of 2 November 2003. The mass actions forced President Shevardnadze to resign before his term in office expired. But very soon after that the crisis was resolved and events developed in compliance with the constitution. And great efforts were made to carry out democratic elections. Yet it is too early to say that we have achieved stability in our election and political system. It should be mentioned that, along with the parties which accumulated vast experience of political struggle in the wake of the Soviet Union’s disintegration, new political structures (or rather political clubs with no clear political platforms and no particular skills for active involvement in politics) appeared in Georgia. Some of the relatively stable parties are falling apart and/or are being split. These varied and chaotic processes were created by the circumstances and our society’s current needs. There can be no ideal parties—they reflect the country’s political climate. In Georgia’s case, we should take into account its historical, political, and economic specifics: the democratic development level, the nation’s mentality, the structure of the electorate, the level of party identification, and the accompanying contradictions and trends. Our political system is far from stable, while many political parties are only stirred to life for a short period during the election race. Parties did not actively show their faces until the 1980s-1990s, since under the communist totalitarian regime they were necessarily clandestine structures. Some of the parties were new; others were inherited (or rather restored) from the period of Georgia’s independence (1918-1921). There were several public organizations (the Rustaveli Society, the Ilia Chavchavadze Society, the Helsinki Union, etc.) which declared their aims to be Georgia’s restored independence and the building of a democratic state.